Teachers Perception Toward the Use of Powtoon Video Animation Media to Increase Students’ Vocabulary Learning Abilities - Trisantiana Nababan (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study investigated PowToon as a technology-based learning media that can utilize the teachers to improve the student's ability in vocabulary learning. The research method used was the descriptive qualitative method. The observation method was used to observe the teachers' actions when teaching vocabulary using PowToon learning media. Furthermore, the interview method was used to collect data about the challenges teachers found when implementing the PowToon video in class. The findings showed that teachers strongly agree that PowToon had a positive perception to implement for students in English class. Through this research, teachers will gain information on technology-based learning media that can be implemented effectively to improve students' vocabulary learning abilities.